1987
DOI: 10.1128/mcb.7.5.1681
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotides in the polyomavirus enhancer that control viral transcription and DNA replication.

Abstract: The polyomavirus enhancer is required in cis for high-level expression of the viral early region and for replication of the viral genome. We introduced multiple mutations in the enhancer which reduced transcription and DNA replication. Polyomaviruses with these mutant enhancers formed very small plaques in whole mouse embryo cells. Revertants of the viral mutants were isolated and characterized. Reversion occured by any of the following events: (i) restoration of guanosines at nucleotide (nt) 5134 and nt 5140 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
77
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 64 publications
4
77
0
Order By: Relevance
“…The abihty of an enhancer to stimulate ori-core dependent DNA replication in a particular mouse cell type correlates closely with its ability to stimulate transcription (Veldman et al 1985;Campbell and Villarreal 1986;Hassell et al 1986;Mueller et al 1988). Mutations that alter one function also alter the other (Linney and Donerly 1983;Tang et al 1987;Martin et al 1988;Satake et al 1988), and cis-acting alterations of the PyV enhancer region can allow viral DNA replication in mouse cells that are normally permissive (Amati 1985). However, some characteristics of enhancers in the PyV origin of replication differ from those of enhancers coupled to promoters.…”
mentioning
confidence: 99%
“…The abihty of an enhancer to stimulate ori-core dependent DNA replication in a particular mouse cell type correlates closely with its ability to stimulate transcription (Veldman et al 1985;Campbell and Villarreal 1986;Hassell et al 1986;Mueller et al 1988). Mutations that alter one function also alter the other (Linney and Donerly 1983;Tang et al 1987;Martin et al 1988;Satake et al 1988), and cis-acting alterations of the PyV enhancer region can allow viral DNA replication in mouse cells that are normally permissive (Amati 1985). However, some characteristics of enhancers in the PyV origin of replication differ from those of enhancers coupled to promoters.…”
mentioning
confidence: 99%
“…The ability of an enhancer to stimulate DNA replication generally follows its ability to stimulate transcription (12,37,64,90). Enhancer mutations that affect on activity also affect promoter activity (55,80,84), and the ability of the Py on to function in a particular mouse cell type depends upon its associated enhancer component (6,12,58,74). Recent studies have demonstrated that Py aux-2 function requires binding of transcription factors (5,7,66,92).…”
mentioning
confidence: 99%
“…These experiments indicated that discrete, noncontiguous elements on the late side of the ori are also required for Py DNA replication in vivo. These sequences map within the Py enhancer region, and the requirement for enhancer function in Py DNA replication was subsequently demonstrated (15,23,51,54). It was therefore of interest to determine whether sequences within the Py enhancer region are required for Py DNA replication in vitro (Fig.…”
mentioning
confidence: 99%
“…Also, the relative affinities of Py and SV40 T Ags for binding sites within their respective ori regions are apparently dissimilar (12,14,28,47). Moreover, while both viruses encode enhancer elements, the Py enhancer is almost directly adjacent to the late boundary of the ori region and consists of a series of discrete elements that bear homologies to other enhancer elements including those of SV40, adenovirus Ela, and mouse immunoglobulin genes (2,22,23,26,31,38,46,51,53). By contrast, the SV40 enhancer, a 72-bp repeated sequence (see reference 22 and references therein), is separated from the core ori by a series of G+C-rich sequences (the 21-bp repeats) that form a distinct transcriptional control element to which the cellular transcription factor, Spl, binds (17) and that is lacking in the Py genome.…”
mentioning
confidence: 99%
See 1 more Smart Citation